Tirzepatide, GIP(1-42) and GIP(1-30) display unique signaling profiles at two common GIP receptor variants, E354 and Q354 - Rees, Tayla A.; Buttle, Benjamin J.; Tasma, Zoe; Yang, Sung-Hyun; Harris, Paul W. R.; Walker, Christopher S. (Frontiers in Pharmacology, 2024)
Type 2 diabetes (T2D) and obesity are prevalent metabolic disorders affecting millions of individuals worldwide. A new effective therapeutic drug called tirzepatide for the treatment of obesity and T2D is a dual agonist of the GIP receptor and GLP-1 receptor. Tirzepatide is clinically more effective than GLP-1 receptor agonists but the reasons why are not well understood. Tirzepatide reportedly stimulates the GIP receptor more potently than the GLP-1 receptor. However, tirzepatide signaling has not been thoroughly investigated at the E354 (wildtype) or Q354 (E354Q) GIP receptor variants. The E354Q variant is associated increased risk of T2D and lower body mass index. To better understand GIP receptor signaling we characterized the activity of endogenous agonists and tirzepatide at both GIP receptor variants. Using Cos7 cells we examined wildtype and E354Q GIP receptor signaling, analyzing cAMP and IP1 accumulation as well as AKT, ERK1/2 and CREB phosphorylation. GIP(1-42) and GIP(1-30)NH2 displayed equipotent effects on these pathways excluding CREB phosphorylation where GIP(1-30)NH2 was more potent than GIP(1-42) at the E354Q GIP receptor. Tirzepatide favored cAMP signaling at both variants. These findings indicate that tirzepatide is a biased agonist towards Gαs signaling and suggests it equally activates the wildtype and E354Q GIP receptor variants. We also observed differences between the pharmacology of the GIP receptor variants with endogenous peptides, which may help to explain differences in phenotype. These findings contribute to a comprehensive understanding of GIP receptor signaling, and will aid development of therapies combating T2D and obesity.